Cp1/cathepsin L is required for autolysosomal clearance in Drosophila. Issue 10 (3rd October 2021) - Xu, Tianqi; Nicolson, Shannon; Sandow, Jarrod J.; Dayan, Sonia; Jiang, Xin; Manning, Jantina A.; Webb, Andrew I.; Kumar, Sharad; Denton, Donna
ABSTRACT: Macroautophagy/autophagy is a highly conserved lysosomal degradative pathway important for maintaining cellular homeostasis. Much of our current knowledge of autophagy is focused on the initiation steps in this process. Recently, an understanding of later steps, particularly lysosomal fusion leading to autolysosome formation and the subsequent role of lysosomal enzymes in degradation and recycling, is becoming evident. Autophagy can function in both cell survival and cell death, however, the mechanisms that distinguish adaptive/survival autophagy from autophagy-dependent cell death remain to be established. Here, using proteomic analysis of Drosophila larval midguts during degradation, we identify a group of proteins with peptidase activity, suggesting a role in autophagy-dependent cell death. We show that Cp1/cathepsin L -deficient larval midgut cells accumulate aberrant autophagic vesicles due to a block in autophagic flux, yet later stages of midgut degradation are not compromised. The accumulation of large aberrant autolysosomes in the absence of Cp1 appears to be the consequence of decreased degradative capacity as they contain undigested cytoplasmic material, rather than a defect in autophagosome-lysosome fusion. Finally, we find that other cathepsins may also contribute to proper autolysosomal degradation in Drosophila larval midgut cells. Our findings provide evidence that cathepsins play an essential role in the autolysosome to maintain basal autophagy flux by balancing autophagosome production and turnover. Abbreviations: 26-29-p: 26-29kD-proteinase; ADCD: autophagy-dependent cell death; Atg8a: Autophagy-related protein 8a; Cp1/cathepsin L: Cysteine proteinase-1; CtsB: Cathepsin B; cathD: cathepsin D; CtsF: Cathepsin F; GFP: green fluorescent protein; LAMP1: lysosomal-associated membrane protein 1; Mitf: microphthalmia associated transcription factor; PCA: principal component analysis; RNAi: RNA interference; RPF: relative to puparium formation